Do Orangutans Have Digestion Problems After Eating Oil Palm Fruit? A Review - Didik Prasetyo; Fitriah Basalamah (Universitas Nasional Jakarta, 2021)
This review discusses the assumptions of orangutans using oil palm by reviewing the daily activities and dietary composition of feeding behavior in wild and ex-rehabilitant orangutans. The percentage pattern of daily activity shows the same trend, spending more time on feeding than other activities. Similarly, the diet composition of wild or ex-rehabilitant orangutans in Sumatera and Borneo show the choice of fruit as their main diet, as a frugivore animals. However, when the fruit season decreases, both wild and ex-rehabilitant orangutans’ choice to use bark or termites to meet their nutritional needs. There are three assumptions in this paper, First, forest fruit scarcity will drive orangutans to utilize other food resources. Second, based on ape dietary studies on oil palm fruit, chimpanzees, orangutans and gorillas preferred bark and young leaves rather than the fruit. Third, health problems arise after consuming oil palm fruit. This is an early sign that nutrients do not drive orangutan to consume oil palm fruit.